Pengelolaan Hutan Produktif untuk Pelestarian Hutan Lampung Menggunakan Operasi Perkalian Modul R^n atas Ring M_n(R) - Nikken Prima Puspita; Fitriani Fitriani; Ahmad Faisol; Lucia Ratnasari (Jurnal Pengabdian Kepada Masyarakat (JPKM) TABIKPUN, 2023)
This activity is in the form of a seminar on productive forest harvesting models. The topic presented is modeling which is done by classifying trees in an area into classes based on their height. Then a two-vector equation model is formulated so that the harvested and unharvested tree configurations are balanced and sustainable and produce an optimal profit. So this model can be used to calculate optimal profit but still pay attention to forest sustainability. Profit is calculated based on three components: harvest vector, non-harvest vector, and Growth Rate matrix. Based on the results of the discussion, there are several obstacles to the model that has been constructed so that it can be used in the Lampung region and become an opportunity for research and collaboration between academics and local government. Furthermore, this forest management model can be modified for fruit-type productive forests such as Lampung coffee or siger avocados which the Lampung Provincial Forestry Service is currently cultivating.